Towards a responsible talent management model. Issue 2 (11th January 2020) - Anlesinya, Alex; Amponsah-Tawiah, Kwesi
Abstract : Purpose: This study aims to critically examine talent management practices and strategies from ethical and responsible management perspectives. Design/methodology/approach: It achieves its aim through conceptual analysis by theorising through the lenses of talent philosophies, the organisational justice theory, the stakeholder theory and extant literature. Findings: A responsible talent management construct and mode to guide the practice of talent management in a socially responsible way is developed. It argues that inclusivity; corporate responsibility; and equity and equal employment opportunity are the key underlying principles of a responsible talent management system. This study further argues that responsible talent management practices promote achievement of multilevel sustainable outcomes such as decent work, employee well-being and organisational well-being. Practical implications: Emphasising responsible management and ethical concerns in organisational talent strategies and practices is non-negotiable, given the current level of interest in sustainable work and employment and in the quest to achieve sustainable human and organisational outcomes through management and organisational practices. Originality/value: The development of a responsible talent management construct and model is original and novel and is expected to shape thinking and drive new research directions in the field of talent management. It further contributes directly to knowledge and practice by demonstrating how organisations can manage their talents in a responsible way.